The coronavirus pandemic: A window of opportunity for sustainable consumption or a time of turning away? - Alexandra Hüttel; Ingo Balderjahn (Journal of Consumer Affairs, 2021)
As a means to preserve present and future generations' living conditions, sustainable consumption presents a route to the enhanced well-being of individuals. However, the occurrence of the COVID-19 pandemic raises the question of whether society is going to continue down a path of increased awareness of sustainable consumption or whether the pandemic will move people to focus more on themselves. Based on data gathered before and near the end of the first pandemic lockdown in Germany in spring 2020, this research demonstrates that ecological, social, and voluntary simplicity consciousness deteriorated in the minds of sustainability-conscious consumers, with notable impacts on their willingness to spend sustainably and their shopping affinity. Furthermore, we identify segments that show particular vulnerability to the lockdown by reacting with a decrease in their ecological consumption consciousness. This study concludes with a discussion of the pandemic's implications for the spread of sustainable consumption styles and human well-being.
Keywords: 650; coronavirus pandemic; intervention study; sustainable consumption; well-being